Catalogue of Cancer Genes – The First Step to Winning the Fight against Cancer - V. Karpov, Dmitry; I. Karpova, Lyubov; I. Vinogradov, Ilya; V. Dmitrienko, Sergey (International Journal of Psychosocial Rehabilitation, 2020)
Performance of an important task of creating a detailed catalogue of cancer genes will allow us to select an optimal cancer therapy for each patient. To catalog cancer genes mutating with high (>20%) and medium (2–20%) frequency, 200 “tumor-norm” pairs on average for each gene should be analyzed, i.e., about 100,000 pairs for the most common types of cancer. Nowadays, the problem is no longer insoluble, since the cost of DNA sequencing has decreased a millionfold over the last 10 years and will continue to decrease more.